Ontogeny and Season Constrain the Production of Herbivore-Inducible Plant Volatiles in the Field - Hare, J. Daniel (Springer-Verlag, 2010)
Herbivores may induce plants to produce an array of volatile organic compounds (herbivore-induced plant volatiles, or HIPVs) after damage, and some natural enemies of herbivores are attracted by those HIPVs. The production of HIPVs by the undomesticated species Datura wrightii was quantified in response to damage by its natural community of herbivores or the plant hormone methyl jasmonate (MeJA) over plant’s 6-month growing season. Patterns of HIPV production were compared to the seasonal abundance of D. wrightii’s two most abundant herbivores, the chrysomelid beetle Lema daturaphila and the mirid bug Tupiocoris notatus, and their shared generalist predator, the lygaeid bug Geocoris pallens. HIPV production was especially high in the spring, when plants were growing vegetatively, but HIPV production declined after plants began to flower and produce fruit, and these volatiles no longer were inducible by September. The composition of the HIPV blends also changed seasonally. HIPV production and composition were partially restored by “rejuvenating” plants back to the vegetative growth stage independently of season by cutting them back and allowing them to resprout and regrow vegetatively. HIPV production of D. wrightii in the field is limited to the earlier ontogenetic stages of growth, despite the fact that both herbivores and their shared natural enemy inhabited plants throughout the full season. The adaptive value of HIPV production in D. wrightii may be constrained by plant ontogeny to the vegetative stages of plant growth. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10886-010-9878-z) contains supplementary material, which is available to authorized users.